Design and implementation considerations for consumer-oriented food subsidies - Rogers, Beatrice (International Food Policy Research Institute, 1988)
The effectiveness and efficiency of a subsidy program depend heavily on the specifics of implementation. Design of subsidy programs should take into account a number of factors, such as political acceptability, leakage of benefits to households outside the target group, cost, and nutritional effectiveness. This chapter discusses specific ways in which these factors can be considered in program implementation and then discusses the relative advantages and disadvantages of the commonest types of food price subsidy programs as they relate to conditions in individual countries.